Upgrading Charcoal Briquettes of Coconut Shell for Export - Diyah Candra Anita; Retno Wulandari; Hendrato Setiabudi Nugroho (Jurnal Pemberdayaan Masyarakat Madani (JPMM), 2020)
The Global Value Chain is an easy way to apply to Small and Medium Enterprises (UKM: Usaha Kecil Menengah) so that they can immediately rise to a higher level. The success of the GVC method can be applied to export-oriented UKM. The goals to be achieved in the community service program Upgrading Export-Oriented Coconut Shell Charcoal Briquettes are as follows: spurring the growth of UKM product exports in Indonesia through competitive market growth, improving management quality of UKM to enter the global market through improving product quality and marketing, accelerating technology transfer and community management of universities to UKM communities, developing synergies between UKM, Universities, Local Governments and the community. The methodology used is upgrading the production process through coordination and scientific discussion, training and simulation, making tools with technology transfer for production efficiency, health checks, and providing tools and facilities to improve employee health. The results of this activity are: increasing the percentage of export volume by expanding production units and adding employees, achieving production efficiency through the technology of permanent conveyor belt machine transfer and oven, forming financial management with Zahir accounting software, training on the use of fire extinguisher and first aid to the employees who get burned, checking employee health, increasing marketing knowledge capacity with English language courses to improve the quality of presentations.